The Value of Summer Studentships to Help Shape Undergraduate Career Trajectories - Page, Rachael; Ferraro, Zachary; Fung Kee Fung, Karen (Université d'Ottawa | University of Ottawa, 2015)
Education level can have a substantial impact on disease risk and is considered a determinant of health. Quality learning experiences, both in- and outside the classroom, may encourage trainees to pursue higher education. Consequently, this could facilitate improvements in personal development and indirectly impact their outlook, motivation, and health status. Thus, students who have positive learning experiences may be more likely to have improved mental and physical health, and be motivated to apply their learnings in a way that positively impacts the health and well-being of others. Summer studentships are an integral part of stimulating students’ interest in science and medicine, and can direct future career endeavours. Many find summer placements beneficial as they give trainees the opportunity to apply classroom knowledge to real-world settings in order to better prepare them for life after undergrad. This commentary aims to inform aspiring medical students of the pros and cons of summer studentships, provide advice on how to overcome challenges they may be faced with during their work term, and encourage trainees to pursue these opportunities to further complement their education so they can develop the necessary skills to help others in the future.
Keywords: studentships; education; undergraduate; medicine; training; experiential learning